Cadmium content in foodstuffs from the Greek market - Karavoltsos, S.; Sakellari, A.; Dimopoulos, M.; Dasenakis, M.; M. Scoullos (Food Additives and Contaminants, 2002)
Determinations of the cadmium content of a wide variety of foodstuffs from the Greek market were carried out. The values detected ranged from <0.1 ng g-1 in alcoholic beverages to 1595.8 ng g-1 in large snails. The highest values were observed in molluscs and crustaceans (117.4ng g-1), followed by leafy vegetables (28.3 ng g-1), potatoes (22.3 ng g-1) and organs and offal (20.7 ng g-1), whereas the other food categories had a lower cadmium content. The results are comparable with those from the rest of Europe. Preliminary analytical data on the cadmium content of food samples of organic cultivation showed significantly lower values compared with those of samples of conventional produce.
Keywords: cadmium; Food contaminants content; Greece; Heavy metal analysis